DIAGNOSING AND ORGANIZING REHABILITATION OF CHILDREN WITH DISABILITIES ON THE AUTISM SPECTRUM - Nigora Azizovna Egamberdiyeva (European Science Publishing, 2024)
This article highlights the factors of ensuring continuity of work on the correct diagnosis of children with autism syndrome, effective organization and conduct of correctional and developmental work that ensures the elimination of deficiencies in behavior and general development, as well as their successful adaptation to social life.
Keywords: autism spectrum defect, ASD, autism syndrome, symptom, stereotype, diagnosis, zone of immediate development of the child, early intervention.